Effects of Spiritual Treatment on the Psychological Well-Being, Spiritual Guidance, and Life Satisfaction Among Visitors of Brazilian Spiritist Centers: An Exploratory Study - Barros e Jorge da Cunha, Carolina Roberta Ohara (International journal of Latin American religions, 2025)
This study aimed to evaluate the effects of spiritual treatment on psychological well-being, life satisfaction, and levels of spiritual guidance among visitors of Brazilian Spiritist centers. An exploratory prospective study with a control group was conducted. Participants in the study group underwent spiritual treatment for 3 weeks and completed questionnaires before and after the treatment. Participants in the control group did not receive spiritual treatment but responded to the questionnaires with the same time interval as the study group. Statistical regression analyses were performed using the R program, employing generalized additive models for location, scale, and shape. A significant increase in psychological well-being was observed following the spiritual treatment, as well as higher levels of spiritual guidance in the group that underwent the spiritual intervention, regardless of the time of assessment. Life satisfaction increased in both groups during the second assessment.